2001
DOI: 10.1523/jneurosci.21-15-05693.2001
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Signal Transduction Pathways in Cerebellar Long-Term Depression by Kinetic Simulation

Abstract: Because multiple molecular signal transduction pathways regulate cerebellar long-term depression (LTD), which is thought to be a possible molecular and cellular basis of cerebellar learning, the systematic relationship between cerebellar LTD and the currently known signal transduction pathways remains obscure. To address this issue, we built a new diagram of signal transduction pathways and developed a computational model of kinetic simulation for the phosphorylation of AMPA receptors, known as a key step for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
141
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(149 citation statements)
references
References 76 publications
(114 reference statements)
7
141
1
Order By: Relevance
“…1, blue arrows) (17-19). Hence, after the Ca 2+ surge, self-regeneration may develop by positive feedback through this closed loop, leading to a rapid, intense activation of PKCα that switches the status of PF-AMPARs from a basal state to the persistently depressed state for LTD (8,20).…”
mentioning
confidence: 99%
“…1, blue arrows) (17-19). Hence, after the Ca 2+ surge, self-regeneration may develop by positive feedback through this closed loop, leading to a rapid, intense activation of PKCα that switches the status of PF-AMPARs from a basal state to the persistently depressed state for LTD (8,20).…”
mentioning
confidence: 99%
“…39 Previous work indicated that activated MAPK goes on to phosphorylate phospholipase A2 (PLA2), which produces arachidonic acid (AA) to further activate PKC and complete the positive feedback loop. [41][42][43] Similar to the study by Antoun et al, the work of Yamamoto et al focused solely on the PKC-MAPK signaling axis, and did not address the potential contribution of RKIP to other signaling pathways that participate in cerebellar LTD induction. For instance, GRK2 has been shown to desensitize the metabotropic glutamate receptor, mGluR1, a key player in cerebellar LTD. 44,45 Future studies should address whether RKIP-dependent modulation of GRK2 activity is working in concert with the PKC-MAPK positive feedback mechanism to drive LTD induction.…”
Section: Rkip and Long-term Depressionmentioning
confidence: 99%
“…However, a considerable number of studies have reported violations of these three requirements under some experimental conditions; consequently, LTD has been questioned several times as the elementary process of cerebellar supervised learning (Llinas et al 1997) and has been postulated for other functions, such as the normalization of total synaptic efficacies on a single Purkinje cell (De Schutter 1995). The kinetic simulation model of LTD signal transduction pathways in a Purkinje cell dendritic spine (figure 5), which has been developed in a series of publications from our group (Kuroda et al 2001;Doi et al 2005;Ogasawara et al 2007) and was recently supported experimentally (Tanaka et al 2007), provided a coherent perspective on these confusing experimental data and competing theoretical hypotheses, and it is introduced in this section.…”
Section: Systems Biology Models Of Cerebellar Ltdmentioning
confidence: 99%
“…In the model proposed by Kuroda et al (2001), the large Ca 2C increase, which is caused by the conjunctive parallel fibre input and the delayed climbing fibre input, induces the activation of linear cascades of phosphorylation of protein kinase C (PKC) followed by phosphorylation and then internalization of AMPA-R, which explains the early phase of LTD up to approximately 10 minutes. On the other hand, the intermediate phase of LTD up to several tens of minutes is mediated by a mitogen-activated protein (MAP) kinase-dependent positive-feedback loop, which consists of PKC, Raf, MAP/extracellular signal-regulated kinase (MEK), MAP kinase, cytosolic phosopholipase A 2 (PLA 2 ), arachidonic acid (AA) and back to PKC (the magenta loop in the middle of figure 5).…”
Section: Systems Biology Models Of Cerebellar Ltdmentioning
confidence: 99%
See 1 more Smart Citation